Impact of COVID19 Pandemic in Bangladesh: A Perspective of Mental Health and Socio-Economic Status - Minhazur Rahman Rezvi; Arju Afrin Kathy; Parvez Mahmood; Azizun Nahar Lima; Zauad Mahmud (UIN Sunan Gunung Djati, 2022)
The COVID-19 pandemic has significantly impacted the global labor market has threatened millions of livelihoods globally including Bangladesh. The study attempts to analyze the emerged socio-economic crisis among street vendors’ households in Bangladesh and to explore the psychological impacts among them during the COVID-19 pandemic. Following the qualitative approach, it was conducted in a total of 16 KIIs from street vendors. The study found that levels of depression and anxiety varied from individual to individual (i.e., street vendors), the households of street vendors with multiple breadwinners or minimum earnings were merely affected by psychological distress whereas the households with single breadwinners or no income had to suffer severe anxiety and depression. Mostly, COVID-19 infected street vendors went through severe mental depression in comparison to others. In conclusion, the paper suggests that policymakers and other respective authorities can effectively address the issues for ensuring the well-being of street vendors in upcoming pandemics.